Fungsi Dalihan Na Tolu Sebagai Sistem Pendidikan Sosial Dalam Kehidupan Masyarakat Mandailing - Husnil Khotimah Harahap; Halimatus Sakdiah; Novita Rahmadani; Nur Maida Sari; Khoirunisa Nasution (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Dalihan Na Tolu is a system of values and norms adhered to by the Mandailing community in North Sumatra. This system not only serves as a guide for life but also as a social education system that shapes the behavior and character of the community. This study aims to examine the function of Dalihan Na Tolu as a social education system in the life of the Mandailing community. The research method used is ethnographic study with a qualitative approach. The results show that Dalihan Na Tolu functions as an effective social education system in shaping the behavior and character of the Mandailing community, promoting values such as mutual cooperation, mutual respect, and responsibility. This study concludes that Dalihan Na Tolu plays an important role in maintaining social harmony and stability in the Mandailing community.